Human-computer interaction : theories, methods, and human issues : 20th International Conference, HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings.: theories, methods, and human issues : 20th International Conference, HCI International 2018, Las Vegas, NV, USA, July 15-20, 2018, Proceedings. Part I (2018) - Unknown
No abstract available